Penilaian Rasio Keuangan, Pertumbuhan Penjualan Dan Tren Dalam Mengukur Kinerja Keuangan Pt. Cisarua Mountain Dairy Tbk Periode 2021–2024 - Ayu, Heliana widya; Mulfi Sandi Yuda; Hardianto, Ade Manggala; Novitasari, Yuli (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2025)
Financial statements are essential nstruments for assessing a company’s condition and performance. This study aims to analyze the financial performance of PT Cisarua Mountain Dairy Tbk (Cimory) for the period 2021–2024 using a descriptive quantitative method through financial ratio and trend analysis. The results show a very high level of liquidity, with an average current ratio of 438.74% and quick ratio of 505.60%, although the cash ratio declined sharply from 433.41% (2021) to 92.09% (2024). Solvency ratios ndicate a healthy condition, with an average Debt to Assets Ratio of 16.47% and Debt to Equity Ratio of 19.40%, reflecting the dominance of equity n the capital structure. Profitability s also strong, with a Net Profit Margin of 17.18%, Return on nvestment of 16.33%, and Return on Equity of 20.10%, providing positive signals for nvestors. Sales growth slowed significantly from 119.97% (2021) to 16.12% (2024), while trend analysis shows ncreases n assets, sales, and net ncome, though accompanied by rising costs that suppressed margins. Overall, Cimory demonstrates solid financial performance, but needs to anticipate declining liquidity and slowing growth through efficiency and nnovation strategies.